Substrates effect on structural and optical properties of indium tin oxide (ITO) thin films by sol gel method - Amirah Athirah, Sazali (2016)
Metallic oxides are one of the transparent semiconductors that having abundant application in industry. Indium tin oxide (ITO) is an example of metallic oxide which commonly referred to ITO thin films. ITO thin films were prepared by sol-gel method and then annealed in the temperature of 500 in order to improve their structural and optical properties. In this study, ITO thin films were deposited on different substrates which are quartz and glass. Characterization techniques of X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), UV-visible, and photoluminescence (PL) spectra measurements were performed to investigate the effects of substrate on the structural and optical properties of ITO thin films. The XRD results indicated that the highest intensity peak for ITO thin film on glass substrate is (222) while ITO thin film on quartz substrate is (211). FESEM characterization showed the grain size for ITO thin film on glass substrate is smaller than grain size of ITO thin film on quartz substrate. Transparency of the films, over the visible light region showed that ITO thin film on quartz substrate has better transparency compared to ITO films on glass substrate as the absorption edge of ITO thin films on quartz substrate shifted towards more longer wavelength compared to absorption edge of ITO thin film on glass substrate. The transmittance spectra showed that the thin film for ITO thin films on glass substrate has highest transmittance than quartz substrate. The optical band gap for ITO thin films on glass substrate and ITO thin films on quartz substrate are 4.30 eV and 4.10 eV respectively. Photoluminiscence (PL) spectra of ITO film deposited on glass and quartz substrate observed strong ultraviolet emission at same value which is only at 580 nm indicating the emission of yellow light.